Współpraca nauki i biznesu w inżynierii produkcji. Tom II - Radwan, Katarzyna; Wrzecioniarz, Piotr; Medyński, Daniel; Gnitecka, Renata; Dąbrowska, Magdalena; Burduk, Anna; Kolbusz, Krzysztof; Małek, Marcin; Grabowski, Marcin; Skoczypiec, Sebastian; Plinta, Dariusz; Korycka-Korwek, Justyna; et al. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The second volume of the series Cooperation between Science and Business in Production Engineering (University of Zielona Góra Press, 2023, eds. J. Patalas-Maliszewska, J. Jakubowski, K. Skrzypek) brings together nine scientific articles presented at the 3rd Conference of the same name, held on 15-16 December 2022 at the Institute of Mechanical Engineering of the University of Zielona Góra. The volume presents research results and good practices in production engineering developed through collaboration between academic institutions and industry.
Keywords: inżynieria produkcji; współpraca nauki i biznesu; transfer technologii; innowacje; Przemysł 4.0; LEAN manufacturing; cyfrowa fabryka; prototypowanie wirtualne; planowanie zasobów ludzkich; doktorat wdrożeniowy; MŚP; production engineering; science-business cooperation; technology transfer; innovation; Industry 4.0; digital factory; virtual prototyping; human resource planning; implementation-oriented doctoral programme; SME